IMPLEMENTASI METODE PEMBELAJARAN TAEM QUIZ DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA SSISWA KELAS IV SD INPRES BONTOMANAI KABUPATEN GOWA - Marsita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low learning outcomes of Pancasila education of grade IV students of SD Inpres Bontomanai. The purpose of this study was to determine the application of the team quiz learning method can improve learning outcomes in the subject of Pancasila education. The type of research used is Classroom Action Research (CAR) which consists of two cycles where each cycle is carried out 3 times. The research procedure consists of four stages in each cycle, namely planning, implementation, observation, and reflection. The subjects in this study were 10 grade IV students of SD Inpres Bontomanai. The results of this study indicate that the application of the team quiz learning method can improve learning outcomes in the subject of Pancasila education of grade IV students of SD Inpres Bontomanai. The increase in learning outcomes is known from the test results in cycle I and cycle II which show an increase in the average and percentage of classical completion. The average score of students in cycle I was 65.4 with classical completion of 30% (3 students) who achieved a score of 75 (KKM score). Cycle II average value is 88.1 with classical completeness of 90% (9 students) who achieved a value of 75 (KKTP). Based on the results of the study above, it can be concluded that the application of the team quiz learning method can improve the learning outcomes of grade IV students of SD Inpres Bontomanai. .